Multitemporal observation of Karla reservoir in Thessaly Greece utilizing SAR and optical remotely sensing imagery - Triantafyllos FALARAS; Maria KOILAKOU; Leonidas TSOUKALAS (European Journal of Geography)
Wetlands constitute areas with significant value and service offerings both in anthropogenic and natural environments. Taking into consideration the importance of studying wetland ecosystems and their changes, the aim of this paper is the observation of Lake Karla’s reservoir fluctuation, since its reconstitution in 2010. For this reason, annual and seasonal fluctuations of the reservoir were estimated, utilizing remote sensing Synthetic Aperture Radar (SAR) (Sentinel 1) and optical (Sentinel 2) imagery, as well as Landsat 5 imagery. For SAR imagery an image segmentation method with a dynamic threshold operator based on mean values is utilized, while for optical imagery the Normalized Difference Water Index (NDWI) is applied. The findings reveal changes in Karla’s reservoir, with its acreage being continually increased on average on an annual basis. Meanwhile, on a seasonal basis, the results indicate some variations in the reservoir, due to precipitation and irrigation purposes.